Synthesis and Characterisation of Some DI & Triorganotin(IV) Derivatives of Schiff Bases - Shukla, P.R.; Bhatt, M.; Misra, M.; Sharma, M.C. (Asian Journal of Chemistry, 2010)
Twenty novel compounds of di and triorganotin (IV) derivatives with two Schiff base ligands derived from furan-2-aldehyde with aniline (L1) and from p-toluidine with glyoxal (L2), have been prepared possessing formulae such as: [Ph2Sn(L1 or L2)X2]; [Ph2Sn (L1 or L2)2]Y2; [Ph3Sn(L1 or L2) X]; [Ph3Sn(L1 or L2)]Y, where X = Cl–, SCN–, Y =ClO4– , BF4–, NO3–. These are assigned six coordinate octahedral or five coordinate trigonal bipyramidal structures respectively on the basis of analytical and spectral studies.